Filamin C Cardiomyopathy Variants Cause Protein and Lysosome Accumulation. Issue 7 (18th August 2021) - Agarwal, Radhika; Paulo, Joao A.; Toepfer, Christopher N.; Ewoldt, Jourdan K.; Sundaram, Subramanian; Chopra, Anant; Zhang, Qi; Gorham, Joshua; DePalma, Steven R.; Chen, Christopher S.; Gygi, Steven P.; Seidman, Christine E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Dominant heterozygous variants in filamin C ( FLNC ) cause diverse cardiomyopathies, although the underlying molecular mechanisms remain poorly understood. Objective: We aimed to define the molecular mechanisms by which FLNC variants altered human cardiomyocyte gene and protein expression, sarcomere structure, and contractile performance. Methods and Results: Using CRISPR/Cas9, we introduced FLNC variants into human induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs). We compared isogenic hiPSC-CMs with normal (wild-type), ablated expression ( FLNC −/− ), or haploinsufficiency ( FLNC +/− ) that causes dilated cardiomyopathy. We also studied a heterozygous in-frame deletion ( FLNC +/Δ7aa ) which did not affect FLNC expression but caused aggregate formation, similar to FLNC variants associated with hypertrophic cardiomyopathy. FLNC −/− hiPSC-CMs demonstrated profound sarcomere misassembly and reduced contractility. Although sarcomere formation and function were unaffected in FLNC +/ − and FLNC +/Δ7aa hiPSC-CMs, these heterozygous variants caused increases in lysosome content, enhancement of autophagic flux, and accumulation of FLNC-binding partners and Z-disc proteins. Conclusions: FLNC expression is required for sarcomere organization and physiological function. Variants that produce misfolded FLNC proteins cause the accumulation of FLNC and FLNC-binding partners which leads to increased lysosome expression and activation of autophagic pathways. Surprisingly, similar pathways were activated in FLNC haploinsufficient hiPSC-CMs, likely initiated by the loss of stoichiometric FLNC protein interactions and impaired turnover of proteins at the Z-disc. These results indicate that both FLNC haploinsufficient variants and variants that produce misfolded FLNC protein cause disease by similar proteotoxic mechanisms and indicate the therapeutic potential for augmenting protein degradative pathways to treat a wide range of FLNC -related cardiomyopathies.